2021
DOI: 10.3389/fsufs.2021.695368
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Comparative Genomics of Salmonella Kentucky Aids Source Tracing and Detection of ST198 and ST152 Lineage-Specific Mutations

Abstract: Non-typhoidal Salmonella (NTS) is a major cause of foodborne illness globally. Salmonella Kentucky is a polyphyletic NTS serovar comprised of two predominant multilocus sequence types (STs): ST152 and ST198. Epidemiological studies have revealed that ST152 is most prevalent in US poultry whereas ST198 is more prevalent in international poultry. Interestingly, ST152 is sporadically associated with human illness, whereas ST198 is more commonly associated with human disease. The goal of this study was to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…According to that study, Clade ST198.2 in the United States has been associated with humans and imported foods, whereas Clade ST198.1 has been isolated from domestically produced food animal products in addition to humans and imported foods (Tate et al, 2022). Among most human clinical cases of Clade ST198.2 Salmonella Kentucky infection in the United States, there is a history of recent travel to Africa, Asia, or Europe (Haley et al, 2019; Soltys et al, 2021). Imported foods from which Clade ST198.2 has been isolated include spices and seafood (Tate et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…According to that study, Clade ST198.2 in the United States has been associated with humans and imported foods, whereas Clade ST198.1 has been isolated from domestically produced food animal products in addition to humans and imported foods (Tate et al, 2022). Among most human clinical cases of Clade ST198.2 Salmonella Kentucky infection in the United States, there is a history of recent travel to Africa, Asia, or Europe (Haley et al, 2019; Soltys et al, 2021). Imported foods from which Clade ST198.2 has been isolated include spices and seafood (Tate et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For many years, it has been the number one serovar isolated from broiler chickens at processing [28, 29] and studies have shown that these are typically isolates belonging to the Kentucky-I lineage [24, 27]. Despite broilers being the largest single reservoir for human cases of Salmonella [30], serovar Kentucky is rarely associated with human clinical cases in the USA [31]. This suggests that humans come into contact frequently with serovar Kentucky-I but that this contact does not result in significant illness.…”
Section: Introductionmentioning
confidence: 99%